Reversible O–H bond activation by an intramolecular frustrated Lewis pair - Vasko, P; Fuentes, MÁ; Hicks, J; Aldridge, S (Royal Society of Chemistry, 2019)
The interactions of the O-H bonds in alcohols, water and phenol with dimethylxanthene-derived frustrated Lewis pairs (FLPs) have been probed. Within the constraints of this backbone framework, the preference for adduct formation or O-H bond cleavage to give the corresponding zwitterion is largely determined by pKa considerations. In the case of the PPh2/B(C6F5)2 system and p-tBuC6H4OH, an equilibrium is established between the two isomeric forms which allows the thermodynamic parameters associated with zwitterion formation via O-H bond cleavage to be probed.